Integrated optical- and acoustic-resolution photoacoustic microscopy based on an optical fiber bundle - Xing, Wenxin (2013)
Photoacoustic microscopy (PAM), whose spatial resolution and maximum imaging depth are both scalable, has made great progress in recent years. However, each PAM system currently achieves only one resolution with an associated maximum imaging depth. Here, we present an integrated optical-resolution (OR) and acoustic-resolution (AR) PAM system implemented by delivering light via an optical fiber bundle. A single fiber core is used to deliver light for OR illumination in order to achieve a small spot size and hence high lateral resolution, whereas all the fiber cores are used to deliver more energy for AR illumination. Most other components are shared by the OR and AR imaging. The lateral resolution can be seamlessly switched between 2.2 μm and 40 μm as the maximum imaging depth is switched between 1.3 mm and 3.0 mm. The system enables automatically co-registered higher-resolution OR and deeper AR photoacoustic imaging.